Pengaruh Model Visual Auditori Kinestetik Berbantuan Dioramaterhadap Pemahaman Konsep IPAS - Putri Rahma Fadhilah; Sari Yustiana (Cahaya Smart Nusantara, 2025)
This research was motivated by the low ability of students to understand concepts in the subject of science and science, students are confused about what first step to take to solve the problem. This study aims to determine the effect of the Visual Auditory Kinesthetic learning model assisted by dioramas on the ability to understand the concept of science of grade III students of SDN Genuksari 02. The instrument used was a test, where the researcher gave a pretest to students before being given treatment and a posttest after being given treatment. This study uses a quantitative approach of the pre-experimental type with a One Group Pretest Posttest design form with 22 students as research subjects. The data analysis technique used was the Paired Sample T-Test through the SPSS 26 program. The results showed that the average pretest score of students 32.36 increased during the posttest to 84.55. The significance value of the Paired Sample T- Test test was 0.000 where 0.000 <0.05. So, it can be concluded that the Visual Auditory Kinesthetic model assisted by dioramas has an effect on the ability to understand the concept of science of grade III students of SDN Genuksari 02